MENINGKATKAN KECERDASAN INTERPERSONAL ANAK USIA 5-6 TAHUN MELALUI PERMAINAN TRADISIONAL - Alexandra Niovani Waluyo; Alis Triena Permanasari; Laily Rosidah (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2017)
Interpersonal intelligence is intelligence that includes many skills in to empathize and understand other people’s thoughts towards achieving the same purposein friendship braid. Traditional games as one form of play activities are believed to be able to provide benefits to children’s interpersonal intelligence in communicating and socializing. This study entitled “Improve the Interpersonal Intellegence Children 5-6 Years Throught Traditional Game” that aims to find out the process of the implementation of the activities of the traditional game play improved interpersonal intelligence, know the ages of 5-6 years. This type of research is research using modelaction Kemmis and McTaggart. Indicator of success in this study way 75%. The research result showed that interpersonal intelligence of children increased to 86% from the results of research of pre 26% rise in cycle I od 58% from the results it can be concluded that the traditional game play acrivities can enhance interpersonal intelligence chidren aged 5-6 years in the PAUD Negeri Terpadu Syeh Malka CIbadak, Lebak-Banten.